2007
DOI: 10.2165/00148581-200709020-00003
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Reuptake Inhibitor-Induced Perinatal Complications

Abstract: There are a growing number of concerns about the utilization of serotonin reuptake inhibitors (SRIs) in late pregnancy and the onset of perinatal complications. This review aimed to analyze and summarize the studies evaluating the risk of perinatal complications (such as low birth weight, preterm delivery, withdrawal or toxic phenomena, and other detrimental events/poor neonatal outcomes) related to maternal SRI use in late pregnancy. A computerized search of MEDLINE (1966-January 2007) and PsycINFO (1974-Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 63 publications
1
12
0
3
Order By: Relevance
“…SSRIs are the most commonly prescribed method of dealing with antenatal as well as postnatal depression. Studies of women who have taken SSRIs while pregnant or lactating have shown some evidence of potential harmful effects on the developing baby during pregnancy (as noted passim in the NICE guidelines), though the decision to treat a pregnant woman remains with the individual practitioner (Cipriani et al 2007;Gentile 2007). chemical changes associated with emotional and frequently gendered states may seem a step toward the acknowledgement of the pathology model, and this may appear to play into the hands of those who would caricature the 'hormonal', depressed woman as malfunctioning and dangerous.…”
Section: Flesh Effectsmentioning
confidence: 99%
“…SSRIs are the most commonly prescribed method of dealing with antenatal as well as postnatal depression. Studies of women who have taken SSRIs while pregnant or lactating have shown some evidence of potential harmful effects on the developing baby during pregnancy (as noted passim in the NICE guidelines), though the decision to treat a pregnant woman remains with the individual practitioner (Cipriani et al 2007;Gentile 2007). chemical changes associated with emotional and frequently gendered states may seem a step toward the acknowledgement of the pathology model, and this may appear to play into the hands of those who would caricature the 'hormonal', depressed woman as malfunctioning and dangerous.…”
Section: Flesh Effectsmentioning
confidence: 99%
“…2005, Gentile 2007a, Belik 2008. Ancak bu belirtiler destek yaklaşımla düzelmekte ve birkaç hafta içinde ortadan kalkmaktadır.…”
Section: Tedaviunclassified
“…Indeed, circulars sent out in 2004 by the FDA, Health Canada, and pharmaceutical sectors highlighted concerns on the use of SSRIs and SNRIs during late pregnancy [21][22][23][24]. Moreover, the FDA issued a second advisory on 19 July 2006, based on evidence showing their use may be linked to persistent pulmonary hypertension of the newborn (PPHN), a potentially life-threatening condition [25].…”
Section: Perinatal Teratogenicitymentioning
confidence: 99%